Ion channels regulating mast cell biology. Issue 5 (22nd April 2013) - Ashmole, I.; Bradding, P.
Summary Mast cells play a central role in the pathophysiology of asthma and related allergic conditions. Mast cell activation leads to the degranulation of preformed mediators such as histamine and the secretion of newly synthesised proinflammatory mediators such as leukotrienes and cytokines. Excess release of these mediators contributes to allergic disease states. An influx of extracellular Ca2+ is essential for mast cell mediator release. From the Ca2+ channels that mediate this influx, to the K+, Cl− and transient receptor potential channels that set the cell membrane potential and regulate Ca2+ influx, ion channels play a critical role in mast cell biology. In this review we provide an overview of our current knowledge of ion channel expression and function in mast cells with an emphasis on how channels interact to regulate Ca2+ signalling.